The Effectiveness of Body-Oriented Psychotherapy: A Review of the Literature - Alexandra Bloch-Atefi; Julie Smith (Psychotherapy and Counselling Journal of Australia)
The purpose of this literature-based review was to review research into the effectiveness of body-oriented and somatic psychotherapies, both in international and Australian settings. A systematic review of internationally published research from the last five years and Australian research from the last 10 years was conducted using the Cochrane Library, Google Scholar, Medline, PsycINFO and PubMed. Overall 19 effectiveness studies and 38 reviews met the inclusion criteria. Body-oriented psychotherapy interventions have been found to be effective in different populations and settings. However, in comparison with more established therapeutic modalities, body-oriented psychotherapy interventions require further empirical research to be deemed effective according to the American Psychiatric Association (APA) standards.